Screening For Lipolytic Bacteria from Bonoloyo Cemetery, Surakarta - Rini, Heni Sulistyo; Tyastuti, Erma Musbita; Siddiq, Yasir; Rahayu, Triastuti (Universitas Labuhanbatu, 2023)
A cemetery is a burial place managed by the government. Inside the TPU, the body is decomposed by microorganisms, one of which is lipolytic bacteria, because the human body is composed of about 12.5–13.60% lipids. Research on lipolytic bacteria from TPU in Indonesia has not been found, even though it has the potential to obtain lipolytic bodies. Therefore, this research was conducted to select lipolytic bacteria from TPU and provide simple assistance. A total of 45 bacterial isolates from TPU Bonoloyo Surakarta were selected for their lipolytic activity using tributyrin agar media. Lipolytic activity was determined using the lipolytic index (LI). Bacterial isolates with lipolytic potential were identified based on colony morphology and Gram staining. The results showed that 30 isolates (67%) showed lipolytic activity, with the highest LI value of 5.43 (BLB 9) after 2x24 hours of incubation. Bacterial isolates that have lipolytic activity are white colonies with circular shapes. The results of Gram staining showed that the bacterial isolates belonged to a group of Gram-negative bacteria in the form of cocci. The conclusion put forward is that public cemeteries (TPU) have the potential to store isolates of lipolytic bacteria dominated by Gram-positive bacteria by as much as 57%